Унгарын билог пайзтай төстэй болох нь - Borbála, Obrusánszky (Historia Mongolarum, 2003)
In the ancient Hungarian history there was an unique object, name is billog, which was used in the justice practice in the Hungarian Kingdom from the Xl-Xlllth century. The orgin of this object is not clear among the Hungarian researchers until now. They tried to explain its usage on the Western European samples, some of them tried to erected from Byzatine Empire. But they investigate this object only formal similarity but not saw its using method. If we are looking at the origin of the word billog, we can find that is has a Altai origin. There is a similar word as beige in Turkish and Mongolian language as well. Beside it, the using method of the Hungarian billog shows its Inner Asian origin. There from the Hun period there was such a object which was used in diplomacy. In the Mongolian period the name of this object became paize or gereg. It can be said that the Hungarian tribes had brought billog from the ancient Inner Asian mother country.